2006
DOI: 10.1577/m05-017.1
|View full text |Cite
|
Sign up to set email alerts
|

Tagging Juvenile Pacific Lamprey with Passive Integrated Transponders: Methodology, Short‐Term Mortality, and Influence on Swimming Performance

Abstract: This study was conducted to determine the feasibility (i.e., efficiency and nonintrusiveness) of tagging juvenile Pacific lampreys Lampetra tridentata with passive integrated transponder (PIT) tags and to determine any associated impacts on survivorship and swimming ability. Juvenile Pacific lampreys were obtained from the John Day Dam fish collection facility and tests were conducted at the Pacific Northwest National Laboratory in 2001 and 2002. A new PIT‐tagging procedure was used to inject 12‐mm tags 5 mm p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
41
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 6 publications
10
41
2
Order By: Relevance
“…Conversely, when healthy fish are reared at high temperature, a rapid increase in bacterial growth may overwhelm the faster response of the immune system [6]. Previous studies reported that significant irritation, infection, and mortality occurred when water temperature increased [7,8]. These results agree with those of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Conversely, when healthy fish are reared at high temperature, a rapid increase in bacterial growth may overwhelm the faster response of the immune system [6]. Previous studies reported that significant irritation, infection, and mortality occurred when water temperature increased [7,8]. These results agree with those of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The untagged groups did not receive electronic tags but had PIT tags inserted into their muscle. This suggests that thermal conditions affect research performance of not only electronic tagging but also conventional tagging [8]. In the East China Sea, releaserecapture studies using conventional tags were conducted during the 1960s and 1970s, and tagged chub mackerel was released during all seasons [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While lamprey are hardy and can be subjected to extended holding without significant mortality, they are also quite susceptible to physical injury. This is particularly true of juveniles, where loss of mucous can result in subsequent fungal infection, particularly in warm water temperature (Mueller et al 2006 been widely used at concentrations of 30-70 ppm (e.g., Stier and Kynard 1986b;Weise and Pajos 1998;Moser and Close 2003). Quintella et al (2004) used 1 ml l -1 2-phenoxyethanol with no mortality of ammocoetes and transforming juveniles.…”
Section: Handling Considerationsmentioning
confidence: 99%
“…No detrimental effect has been found on survival (Bolland, Cowx, & Lucas, 2009;Navarro et al, 2006;Ombredane, Baglinière, & Marchand, 1998), growth (Acolas, Roussel, Lebel, & Baglinière, 2007;Knaepkens, Maerten, Tudorache, De Boeck, & Eens, 2007;Lee, Park, & Cho, 2009), reproduction (Baras, Malbrouck, Houbart, Kestemont, & Mélard, 2000;Mahapatra et al, 2001), feeding behavior (Newby, Binder, & Stevens, 2007;, and swimming ability (Moore, Russell, & Potter, 1990;Mueller, Moursund, & Bleich, 2006;). The few studies on snakes have shown that PIT-tagging does not affect growth, movement, and speed (Keck, 1994;Jemison et al, 1995).…”
mentioning
confidence: 96%